2021
DOI: 10.3389/fonc.2021.569295
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Mediates the Apoptosis of Triple Negative Breast Cancer Cells by Reducing POLD1 Expression

Abstract: Resveratrol (RSV) is known to possess anticancer properties in many types of cancers like breast cancer, in which POLD1 may serve as a potential target. However, the anticancer mechanism of RSV on triple negative breast cancer (TNBC) remains unclear. In the present study, the antitumor effects and mechanism of RSV on TNBC cells were analyzed by RNA sequencing (RNA-seq), which was then verified via cell counting kit-8 (CCK8), immunofluorescence, immunohistochemistry, Western Blot (WB), flow cytometry, and hemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 58 publications
0
25
0
Order By: Relevance
“…Li et al (2017b) demonstrated that the mechanism of apoptosis induced by liriodenine in MCF-7 cells inhibited the expression of Bcl-2, cyclin D1, and vascular endothelial growth factor (VEGF) and upregulated the level of p53. As shown in the study by Liang et al (2021), resveratrol can facilitate TNBC cell apoptosis via the p53mediated pathway. In 2021, a study by Vazhappilly et al indicated that catechol could inhibit proliferation and result in apoptosis in MCF-7 cells by activating p53, inhibiting of regulatory proteins such as DNMT1, P-BRCA1, Mcl-1, and PDCD6, and increasing the Bax/Bcl-2 ratio.…”
Section: Mitochondrial Pathway-mediated Apoptosismentioning
confidence: 78%
“…Li et al (2017b) demonstrated that the mechanism of apoptosis induced by liriodenine in MCF-7 cells inhibited the expression of Bcl-2, cyclin D1, and vascular endothelial growth factor (VEGF) and upregulated the level of p53. As shown in the study by Liang et al (2021), resveratrol can facilitate TNBC cell apoptosis via the p53mediated pathway. In 2021, a study by Vazhappilly et al indicated that catechol could inhibit proliferation and result in apoptosis in MCF-7 cells by activating p53, inhibiting of regulatory proteins such as DNMT1, P-BRCA1, Mcl-1, and PDCD6, and increasing the Bax/Bcl-2 ratio.…”
Section: Mitochondrial Pathway-mediated Apoptosismentioning
confidence: 78%
“…All these mechanisms are related to the activation of the p53 oncosuppressor, a transcription factor involved in cell cycle regulation and apoptosis [111]. This was recently confirmed by Liang and colleagues, who demonstrated through RNA sequencing that genes affected by resveratrol treatment in MDA-MB-231 cells were mainly involved in apoptosis and the p53 signaling pathway [82].…”
Section: Effect Of Resveratrol On Other Carcinogenic Pathwaysmentioning
confidence: 80%
“…Reduced angiogenesis [81,82] Phosphorylation or acetylation of p53 at the level of the serine residue 15…”
Section: Resveratrol and Free Radicalsmentioning
confidence: 99%
“…In contrast, ruthenium (II)/allopurinol complex binds to tumor cells to cause DNA damage and upregulate p53 protein, then causing the overexpression of bim, beclin-1 and caspase-3, and ultimately induced cell apoptosis [ 121 ]. Additional small-molecule compounds target p53 protein to induce apoptosis in TNBC cells [ 122 126 ] (Table 1 ).…”
Section: Targeting Apoptotic Pathways With Small-molecule Compounds I...mentioning
confidence: 99%